Correlation between Antistress and Hepatoprotective Effects of Schisandra Lignans Was Related with Its Antioxidative Actions in Liver Cells. (18th June 2012) - Pu, Hao-Jie; Cao, Yun-Feng; He, Rong-Rong; Zhao, Zhi-Long; Song, Jin-Hui; Jiang, Bin; Huang, Ting; Tang, Shu-Hong; Lu, Jian-Min; Kurihara, Hiroshi
Abstract : The present study was conducted to investigate the relationship between the anti-stress and hepato-protective effects of Schisandra Lignans Extract (SLE) on stress-induced liver damage. Seven weeks old male mice were fixed in a restraint tube for 18 h to induce liver damage. SLE was orally administered to animals for 5 days at dosages of 100 and 200 mg/kg/day before exposed to restraint stress. Oral administration of SLE significantly reduced restraint-induced liver damage in experimental animal. SLE was further found to significantly alleviate the provocation of corticosterone in stressed mice. SLE also significantly decreased oxidative damage and increased anti-oxidative capability of liver cells by preventing the over production and accumulation of free radicals. In conclusion, the protective effects of SLE on stress-induced liver damage were confirmed, and the correlation between hepatoprotective and anti-stress effects of schisandra lignans was possible related to its alleviation on the malignant effects of stressors for bio-homeostasis, such as balance of oxidation and reduction in cells.